Hydrocephalus Due to Neurocysticercosis in the Cerebral Aqueduct: Case Report - Dória, Felipe Meireles; Teixeira, Lívia Novaes; Freitas, Matheus Costa; Rocha, Isabella Versiani Martins; Mendes, Raquel Cordeiro; Bastelli, Bárbara (Brazilian Journal of Case Reports, 2026)
Neurocysticercosis (NCC) is the leading cause of parasitic infection of the central nervous system, resulting from infestation by the larval stage of Taenia solium. Intraventricular forms of the disease, although less frequent, are associated with high morbidity and mortality, mainly due to obstruction of cerebrospinal fluid flow and consequent hydrocephalus. We report the case of a patient previously diagnosed with NCC who presented with acute clinical deterioration secondary to obstruction of the cerebral aqueduct by a cyst compatible with a cysticercus, a location rarely described in the literature. The patient underwent emergency neurosurgical intervention with good clinical outcome. Antiparasitic therapy was not initiated, considering the high number of viable lesions and the risk of an exacerbated inflammatory response. This case report reinforces the importance of early diagnosis of complications associated with NCC, particularly ventricular forms, and expands knowledge of atypical topographic presentations, contributing to improved clinical recognition and appropriate management of the disease.